Multipolarization or Cosmopolitanization? Moving Towards an Indeterminate World - Jong, Abbas (Sotsiologicheskoe Obozrenie / Russian Sociological Review, 2024)
In academic and public policy discourses, there is an increasing discussion about the emergence of a multipolar world order. This discussion is supported by statistical data, historical evidence, and concrete facts that highlight the polarization of the world and the waning influence of American hegemony. These narratives often frame the current state of the world as a transition from one certain and determinate order to another. The purpose of this paper is to critically grapple with the concept of world order, which serves as the foundation for many theories in the fields of globalization and international relations. A critical review of the dominant theories of world order and globalization reveals that many of them presuppose the existence of a regulated entity for the imaginary unity of the world, whether positively or negatively. This presupposition is prominent due to the pervasive influence of the epistemological antinomy of foundationalism/anti(non)-foundationalism. By suspending this antinomy and deconstructing the idea of world order, drawing upon the theory of risk society and cosmopolitanization as a new global differentiation force this paper argues that the contemporary world is not moving towards a new, predetermined order but rather towards a state of indeterminacy, uncertainty, and fluidity. The rise of global risks in recent times has instigated a transformational process that has affected various aspects of different societies. This paper argues that understanding and interpreting the current state of the world requires a revision of our epistemology and a shift towards prioritizing the indeterminate that is risk.